The Use of Visual Imagery Strategy to Improve The Students’ Writing Skill of Recount Text at The Tenth Grade of Senior High School - Siti Andrianti Marpaung (VISION, 2021)
This research was aimed to determine the impact of using Visual Imagery strategy in enhancing the students' writing skill. The subjects of this research were the students of class X MA. Laboratory UIN SU Medan for the 2020/2021 academic year, which consists of 40 students. This research was conducted by doing a classroom action research using two cycles. Each cycle consists of planning, acting, observing, and reflecting. The data obtained through quantitative and qualitative data. The quantitative data were obtained from tests which included pre-test, post-test I, and post-test II. Meanwhile, the qualitative data were obtained from interviews and observation sheets. The results of the data analysis showed that there was an enhancement on the students' writing achievements from each cycle. The results can be seen from the mean score of students in the pre-test 50.85 increased to 69.4 in the post-test I and increased to 79.3 in the post-test II. In the pre-test, 10% (4 of 40 students) scored > 75. In the first post-test there were 55% (22 of 44 students) who scored > 75. In the second post-test, there were 90% (36 of 40 students) who get a value > 75. To verify the hypothesis using the t-test formula, the results of the t-test obtained t observation (8.60) > t table (1.684). Thus, the alternative hypothesis (Hα) can be accepted. Based on these findings, the alternative hypothesis (Hα) states that the use of visual imagery strategies can improve students' ability to write recount text.